2022
DOI: 10.1084/jem.20212434
|View full text |Cite
|
Sign up to set email alerts
|

Differential IL-12 signaling induces human natural killer cell activating receptor-mediated ligand-specific expansion

Abstract: IL-12 is an essential cytokine involved in the generation of memory or memory-like NK cells. Mouse cytomegalovirus infection triggers NK receptor-induced, ligand-specific IL-12–dependent NK cell expansion, yet specific IL-12 stimulation ex vivo leading to NK cell proliferation and expansion is not established. Here, we show that IL-12 alone can sustain human primary NK cell survival without providing IL-2 or IL-15 but was insufficient to promote human NK cell proliferation. IL-12 signaling analysis revealed ST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 66 publications
(114 reference statements)
0
23
0
Order By: Relevance
“…We further showed that TGFβ or IFNα stimulation suppressed FcRγ upregulation independently of mTOR or FOXO1 activity ( Viel et al, 2016 ; Platanias, 2005 ). This shows that besides mTOR activation and FOXO1 suppression, other signaling pathways, such as Smad signaling ( Viel et al, 2016 ) or STAT1 signaling ( Platanias, 2005 ), which are reported to inhibit NK cell proliferation, suppress FcRγ expression ( Liu et al, 2020 ; Krämer et al, 2021 ; Witkowski et al, 2021 ; Shemesh et al, 2022 ). In line with these results, we showed that the increase in mature NK cells with an adaptive-like phenotype during COVID-19 infection is associated with increased TGFβ and IFNα levels and increased disease severity.…”
Section: Discussionmentioning
confidence: 93%
“…We further showed that TGFβ or IFNα stimulation suppressed FcRγ upregulation independently of mTOR or FOXO1 activity ( Viel et al, 2016 ; Platanias, 2005 ). This shows that besides mTOR activation and FOXO1 suppression, other signaling pathways, such as Smad signaling ( Viel et al, 2016 ) or STAT1 signaling ( Platanias, 2005 ), which are reported to inhibit NK cell proliferation, suppress FcRγ expression ( Liu et al, 2020 ; Krämer et al, 2021 ; Witkowski et al, 2021 ; Shemesh et al, 2022 ). In line with these results, we showed that the increase in mature NK cells with an adaptive-like phenotype during COVID-19 infection is associated with increased TGFβ and IFNα levels and increased disease severity.…”
Section: Discussionmentioning
confidence: 93%
“…We further showed that TGFβ or IFNα stimulation suppressed FcRγ upregulation independently of mTOR or FOXO1 activity (Viel et al, 2016;Platanias, 2005). This shows that besides mTOR activation and FOXO1 suppression, other signaling pathways, such as Smad signaling (Viel et al, 2016) or STAT1 signaling (Platanias, 2005), which are reported to inhibit NK cell proliferation, suppress FcRγ expression (Liu et al, 2020;Krämer et al, 2021;Witkowski et al, 2021;Shemesh et al, 2022). In line with these results, we showed that the increase in mature NK cells with an adaptive-like phenotype during COVID-19 infection is associated with increased TGFβ and IFNα levels and increased disease severity.…”
Section: Discussionmentioning
confidence: 60%
“…NK cell proliferation or expansion is regulated by IL-2, IL-15, and IL-12 (Wang and Zhao, 2021;Wiedemann et al, 2020;Shemesh et al, 2022), by the phosphorylation of STAT5 (pSTAT5), STAT4 (pSTAT4), and other STATs directly or indirectly, and by the activation of mammalian target of rapamycin (mTOR) complexes (Marçais et al, 2014;Anton et al, 2015;Anton et al, 2020). Activation of the mTOR complex-1 (mTORC1) leads to ribosomal protein S6 phosphorylation at position S235/236 (pS6S235/236) and regulates cap-dependent protein translation and cell cycle progression (Marçais et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fujii R observed that the IL-15SA/IL-15RA complex can act as an inhibitor to block the inhibitory effects of TGF-β on the NK cell activation markers CD226, NKG2D, and NKp30 in breast, lung, and prostate cancers ( 87 ). IL-12 is an essential cytokine involved in the generation of memory-like NK cells, and IL-12 alone can sustain human primary NK cell survival without providing IL-2 or IL-15 but is insufficient to promote human NK cell proliferation ( 88 ). NK cells in breast tumors express high levels of NKG2A and low levels of NKp46, perforin, and granzyme B.…”
Section: Regulatory Mechanisms and Research Strategies Of Nk Cells An...mentioning
confidence: 99%